Disputes between US vs Iran regarding nuclear issues: Harian Analisa coverage, Indonesia - ABDUL RANI, U; HAMDANI, M.S.; AZMAN, S (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT Several strengths play a part to produce the facts, such as readers, ideology, organization, and economic reputation are of those variables that affect the contents of the news. The Harian Analisa newspaper whose owner is a Muslim and its audience is the Indonesian Islamic community, affects the ideology possessed by this newspaper as an ideology of defense to Muslim citizens. So, it can be undoubtedly assumed that the news presented in it regarding the disputed between America and Iran will carry protection to Iran as the majority of its citizens is Muslim.RESUMEN Una serie de fortalezas que juegan un papel importante para producir los hechos, como lectores, ideología, organización y reputación económica, son las variables que afectan el contenido de las noticias. El periódico Harian Analisa, cuyo dueño es musulmán y su audiencia es la comunidad islámica indonesia, afecta la ideología que posee este periódico como ideología de defensa para los ciudadanos musulmanes. Por lo tanto, se puede suponer indudablemente que las noticias presentadas en relación con la disputa entre Estados Unidos e Irán llevarán una defensa a Irán, ya que la mayoría de sus ciudadanos son musulmanes.